2000
DOI: 10.1034/j.1399-5618.2000.020111.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of obsessive‐compulsive disorder in recovered inpatients with bipolar disorder

Abstract: Our findings suggest that BD-II, OCD, dysthymia, and suicidality cluster together in some subjects with BD. We discuss the clinical implications of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 33 publications
3
55
1
4
Order By: Relevance
“…In the ECA database, OCD-BD patients had statistically significant higher lifetime rates of 'thoughts of suicide', 'suicide attempts', 'thoughts of death', and 'wanting to die' vs. non-OCD-BD patients (3). These features were confirmed in most recent studies both in OCD-BD patients (31,37,39,75) and in BD-OC syndrome patients (16). OCD also was associated with a 2.4-fold increase in the odds of suicidal ideation among BD adolescents as compared to noncomorbid adolescents (45).…”
Section: Included Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…In the ECA database, OCD-BD patients had statistically significant higher lifetime rates of 'thoughts of suicide', 'suicide attempts', 'thoughts of death', and 'wanting to die' vs. non-OCD-BD patients (3). These features were confirmed in most recent studies both in OCD-BD patients (31,37,39,75) and in BD-OC syndrome patients (16). OCD also was associated with a 2.4-fold increase in the odds of suicidal ideation among BD adolescents as compared to noncomorbid adolescents (45).…”
Section: Included Studiessupporting
confidence: 80%
“…Three populationbased studies conducted in Italy and USA, reported lifetime prevalence rates of comorbid OCD in BD patients ranging between 11.1% and 21% (3,23,24). In hospital-based studies, the lifetime prevalence of comorbid OCD in BD patients ranged between 1.8% and 35.1% (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) depending on the features of the BD study population included (schizoaffective disorder, bipolar type). When restricting the analysis to studies with sample size greater than 250, the OCD-BD prevalence range was narrower (3-13.6%) (24,26,27,31,38,39), and the mean prevalence rate of BD-I comorbidity was 15%, while BD-II was 12.6% (24,38,39).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When diagnosed comorbidly with BD, OCD has been associated with an earlier onset of BD, a higher number of previous mood episodes, rapid cycling, seasonality, substance misuse, and lower overall functioning 732, 737, 738, 739, 740, 741, 742. Jeon et al recently conducted a comprehensive review of patients diagnosed with BD and comorbid OCD and found twice the rate of pharmacological switch to mania or hypomania, but suggested this could be due to the more frequent use of antidepressants in that population 732.…”
Section: Specific Populationsmentioning
confidence: 99%
“…[1][2][3] The prevalence of OCD may be masked by presence of manic or depressive symptoms in BD, which is evident from data in remitted patients where the reported prevalence of comorbid OCD is quite high (35 to 38.6%). [4][5][6] In children with BD, the prevalence of OCD ranges between 20.7 and 46.9%. 7 The high prevalence of such association is even argued for a specific subtype of BD or OCD or one disorder increasing the propensity to develop the other.…”
Section: Introductionmentioning
confidence: 99%